Narratives of incarcerated women in a Prison in Malawi: a qualitative study - Ellen Samwiri Nkambule; Balwani Chingatichifwe Mbakaya (BMC Women's Health)
Abstract Background In Malawi, women in prisons make up 2.7% of the total prison population. However, the experiences of women incarcerated are not well documented in the literature. We aim to describe the experiences of women incarcerated in a Malawian prison facility. We will concentrate on the qualitative findings that highlight the unique perspectives of these women, including those in which they are imprisoned alongside their children, as well as the larger implications for child welfare and prison policy. Methods A qualitative approach using descriptive study design was used to explore the experiences of incarcerated women in prisons in Malawi. In-depth interviews were conducted with seven incarcerated women (n = 7). The interviews followed a semi-structured interview guide, and the data were analyzed manually using thematic analysis. Results The following four themes emerged from the data: the burden of conviction, prison as a traumatic environment, health insecurity and perceptions regarding release from prison. Participants reported that being convicted caused significant psychosocial stress. The incarcerated women stated that they are subjected to inhumane and degrading treatment. The prison conditions are poor. The nutrition is inadequate for both incarcerated women and their children. Incarcerated women look forward to their release, citing that they have been transformed and are optimistic about their new lives. Prison living made them calmer and more patient. Others express concern that the stigma of incarceration will inhibit their ability to reconnect with the community upon release. Conclusion Understanding women’s experiences in Malawian prisons can inform policy and improve standards of living for incarcerated women in Malawian prisons.